PROTOCOL: key characteristics of effective preschool-based interventions to promote self-regulation: a systematic review and meta-analysis - Kanayama, A; Siraj, I; Moeyaert, M; Steiner, K; Yu, EC; Ereky-Stevens, K; Iwasa, K; Ishikawa, M; Kahlon, M; Warnatsch, R; Dascalu, A; He, R; et al. (Wiley, 2024)
This is the protocol for a Cochrane Review. The objectives are as follows: The aim of this systematic review is to advance our understanding of the key characteristics of effective preschool-based interventions designed to foster self-regulation. To accomplish this, the review addresses the following questions: 1. What types of preschool-based interventions have been developed to promote self-regulation? 2. What is the average effect of these preschool-based interventions on self-regulation, focusing on four key constructs: integrative effortful control, integrative executive function, self-regulation, and self-regulated learning? 3. What characteristics-such as Resource Allocation, Activity Type, and Instruction Method-could potentially contribute to the effects of preschool-based interventions in promoting self-regulation?